Alguém pode me explicar como se faz essa conta 3a(a-b)-2a(a+b) ???
Soluções para a tarefa
Respondido por
1
3a(a - b) - 2a(a + b)
3a² - 3ab - 2a² - 2ab
3a² - 2a² - 3ab - 2ab
a² - 5ab
3a² - 3ab - 2a² - 2ab
3a² - 2a² - 3ab - 2ab
a² - 5ab
Respondido por
0
Olá ,
Resolução :
=> 3a(a - b) - 2a(a + b)
=> 3a^2 - 3ab - 2a^2 - 2ab
=> (3-2)a^2 (-3-2)ab
=> a^2- 5ab
Resposta :. a^2 - 5ab
Bons Estudos!!
Resolução :
=> 3a(a - b) - 2a(a + b)
=> 3a^2 - 3ab - 2a^2 - 2ab
=> (3-2)a^2 (-3-2)ab
=> a^2- 5ab
Resposta :. a^2 - 5ab
Bons Estudos!!
Perguntas interessantes
Geografia,
1 ano atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás
História,
1 ano atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás
Química,
1 ano atrás